2021
DOI: 10.1186/s40834-020-00146-1
|View full text |Cite
|
Sign up to set email alerts
|

Influences on contraceptive method choice among adolescent women across urban centers in Nigeria: a qualitative study

Abstract: Background Despite calls to increase contraceptive use among adolescents and youth, large gaps still exist, creating an unmet need for family planning. Past research has focused on barriers to seeking a method. There is less understanding of the types of methods young women want and who and what influences these decisions. This study examines what method characteristics young Nigerian women prioritize when choosing a method to inform future family planning programming. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…For example, some parents, particularly mothers, feel very uncomfortable discussing sexuality and contraception with their own children who are of childbearing age due to cultural norms. Similar findings have been documented by Samandari et al in (28,37,38).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For example, some parents, particularly mothers, feel very uncomfortable discussing sexuality and contraception with their own children who are of childbearing age due to cultural norms. Similar findings have been documented by Samandari et al in (28,37,38).…”
Section: Discussionsupporting
confidence: 92%
“…For example, some parents, particularly mothers, feel very uncomfortable discussing sexuality and contraception with their own children who are of childbearing age due to cultural norms. Similar findings have been documented by Samandari et al in Niger in 2019, Ezenwaka et al in Nigeria in 2020, and Sanchez et al in Nigeria also in 2021, who found barriers such as religious beliefs and lack of autonomy in contraceptive use by adolescents and youth ( 28 , 37 , 38 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Even though adolescent girls discuss contraceptive use with their intimate partners, these conversations are usually to provide approval for contraceptive use [ 20 , 51 ], which is linked to the unequal gender power dynamics in relationships, with males ultimately controlling the decision making on contraceptive use [ 51 ]. They also influence the choice of contraceptive method, which typically aligns with their preferred method [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though adolescent girls discuss contraceptive use with their intimate partners, these conversations are usually to provide approval for contraceptive use (18, 53), which is linked to the unequal gender-power dynamics in relationships with males ultimately controlling the decision-making on contraceptive use (53). They also in uence the choice of contraceptive method, which typically aligns with their preferred method (54).…”
Section: Interpersonal In Uencersmentioning
confidence: 99%